Clinicopathological analysis of HPV‐related and non‐HPV‐related oral/oropharyngeal squamous cell carcinoma - WANG Xiaoling; QIANG Jinbiao; QU Ming; ZHANG Yuqing; QIAO Chunyan; ZHANG Zebing; SHI Ce (Kouqiang hemian waike zazhi)
[Objective:] To make a clinicopathological analysis of human papilloma virus (HPV)‐related and non‐HPV‐related oral/oropharyngeal squamous cell carcinoma (OSCC/OPSCC) diagnosed in our hospital, and to further understand the differences between the two diseases in clinical and pathological aspects. [Methods:] The cases of OSCC/OPSCC diagnosed from December 1, 2018 to November 30, 2021 in the Hospital of Stomatology, Jilin University were collected. The diagnoses of HPV‐related and non‐HPV‐related squamous cell carcinoma were made based on the detection of p16 by immunohistochemical staining, HPV DNA by polymerase chain reaction (PCR), and high‐risk HPV subtypes by PCR‐reverse dot hybridization. Statistical analyses were made according to the basic information, clinical characteristics, and pathological manifestations of patients. [Results:] There was a significant difference in the depth of invasion (DOI) between HPV‐related and non‐HPV‐related OSCC; there was a statistical difference between HPV‐related and non‐HPV‐related OPSCC in terms of the Ki‐67 positive rate, whether over 70% or not. [Conclusion:] To distinguish HPV‐related and non‐HPV‐related OSCC/OPSCC in diagnosis so as to provide a basis for the selection of treatment options and a reference index for the prognosis of patients, and enrich the clinicopathological data in the field of HPV‐related head and neck squamous carcinoma (HNSCC), thus improve the knowledge of HPV‐related OSCC/OPSCC.